2018
DOI: 10.1109/tcsi.2017.2759340
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Simplified Frequency-Domain Volterra Models With Quasi-Sinusoidal Input

Abstract: The Volterra approach to the modeling of nonlinear systems has been employed for a long time thanks to its conceptual simplicity and flexibility. Its main drawback lies in the number of coefficients, which rapidly grows with memory length and nonlinearity order. In some important cases, such as power system applications, the input signal is periodic and contains a fundamental component that is much larger with respect to the others. This peculiarity can be exploited in order to dramatically reduce the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…As pointed out in the introduction, the authors already presented in [18], [19] a simplification of frequency-domain Volterra models devoted to the behavioral representation of power system devices. In particular, the number of coefficients can be greatly reduced thanks to the peculiar spectral content of electrical quantities in AC power systems, consisting of a strong fundamental tone, and harmonics that are much smaller in amplitude.…”
Section: Frequency Domain Modeling Of Nonlinear Power System Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out in the introduction, the authors already presented in [18], [19] a simplification of frequency-domain Volterra models devoted to the behavioral representation of power system devices. In particular, the number of coefficients can be greatly reduced thanks to the peculiar spectral content of electrical quantities in AC power systems, consisting of a strong fundamental tone, and harmonics that are much smaller in amplitude.…”
Section: Frequency Domain Modeling Of Nonlinear Power System Devicesmentioning
confidence: 99%
“…In [19] the authors have validated the proposed simplification that has been applied to the behavioral representation of several nonlinear power system devices by means of numerical simulations. In this paper, the approach has been experimentally tested to model the steady-state behavior of medium voltage (MV) instrument transformers, namely to predict their secondary voltage harmonics (system output) produced by a known primary voltage (system input).…”
Section: Frequency Domain Modeling Of Nonlinear Power System Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the case of CTs, also the metrological performance of conventional voltage transformers (VTs) employed for harmonic measurement is strictly related to their dynamic and nonlinear behavior [ 23 ]. In this respect, the authors of the present paper have shown that nonlinear behavioral models based on a simplified Volterra representation [ 24 , 25 ] can be used to accurately predict the secondary voltage spectrum from the primary side [ 26 ]. This enables a thorough characterization of VTs: linear and nonlinear effects can be separated, nonlinearities can be classified, and their individual impact on the overall metrological performance can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods for harmonic analysis in the frequency domain and time domain are currently present in the relevant literature; hybrid frequency and time-domain methods have also been developed [2]- [14]. Medina et al [2] present a review with a concise description and analysis of the fundamentals, characteristics, analytical details, merits, and drawbacks associated with existing methods in frequency and time domains for harmonic analysis in practical power networks.…”
Section: Introductionmentioning
confidence: 99%